Automatic SMS Reader for Visually Impaired People - G.Jhansi Rani,Ms.Banala Saritha,K.Mahender (International Journal of Advanced Science and Technology, 2020)
Mobility is becoming need of the hour and connectivity is the key for its development. Visually impaired people face struggles during mobility and also in connectivity. Several research works were undertaken by bountiful researches across the globe to enable visually impaired people getting connected for their day to day activities. In this work we have made an attempt to develop a fully automatic message reader system using raspberry pi. A specific algorithm and machine coding is used in this system which will convert text into voice, which in turn can be stored, retrieved and further processed if necessary. Python script is employed to develop encoding system and GSM module connects the text to audio output. Through this system rapid conversation of text to voice is possible and this can be further extended using specific modules.